(3TjN GdESdGe YHO dWQje Gdachf OGYjI GdSdajI (B/s - (3SYO Gddg,CHh GdbGSe s ((3dHfGf (B:s (3OGQ GdYQH GdESdGej ,s, 1986)
(3MjGI GdTjN YHO GdcQje Gdachf h fTGJg h KbGaJg hXGFag h GeJjGRGJg h ecGfGJgs
Keywords: (3YHO GdcQje Gdachfs